2023
DOI: 10.1007/s12035-023-03493-7
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant SARS-CoV-2 Spike Protein and Its Receptor Binding Domain Stimulate Release of Different Pro-Inflammatory Mediators via Activation of Distinct Receptors on Human Microglia Cells

Abstract: SARS-CoV-2 infects cells via its spike (S) protein binding to its surface receptor Angiotensin ConvertingEnzyme 2 (ACE2) on target cells and results in acute symptoms involving especially the lungs known as COVID-19. However, increasing evidence indicates that SARS-CoV-2 infection produces neuroin ammation associated with neurological, neuropsychiatric, and cognitive symptoms persists well past the resolution of the infection, known as post-COVID-19 sequalae or Long-COVID. The neuroimmune mechanism(s) involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 127 publications
1
1
0
Order By: Relevance
“…Similar levels of the S protein from the SARS 2003 epidemic were reported to have proinflammatory effects [ 24 ]. Moreover, this dosage was in tune with studies from other groups [ 6 , 25 , 26 ]; however, it was higher that the levels of the S1 protein in plasma samples of COVID-19 patients, which was up to 100 pg/ml [ 27 ]. Heat-treated forms of these proteins were generated by heating for 5 min at 95 °C.…”
Section: Methodssupporting
confidence: 57%
“…Similar levels of the S protein from the SARS 2003 epidemic were reported to have proinflammatory effects [ 24 ]. Moreover, this dosage was in tune with studies from other groups [ 6 , 25 , 26 ]; however, it was higher that the levels of the S1 protein in plasma samples of COVID-19 patients, which was up to 100 pg/ml [ 27 ]. Heat-treated forms of these proteins were generated by heating for 5 min at 95 °C.…”
Section: Methodssupporting
confidence: 57%
“…We also show that microglia release MMP-9 when stimulated by SARS-CoV-2 Spike protein. We had previously reported that SARS-CoV-2 Spike protein stimulated cultured human microglia to secrete IL-1b, IL-18 and protein S100B, associated with brain damage (Tsilioni and Theoharides, 2023) The neurological issues of Long-COVID may be attributed to the SARS-CoV-2 Spike protein (Theoharides and Kempuraj, 2023) since SARS-CoV-2 has not been shown to infect brain cells. In articular, a recent study demonstrated that SARS-CoV-2 has limited potential to proliferate in the brain and was unable to transmit between synaptic axons neurons in a human stem cell-derived neuronal culture system (Luczo et al, 2024).…”
Section: Discussionmentioning
confidence: 99%